2019
DOI: 10.1016/j.aprim.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Mantenimiento de la lactancia materna exclusiva a los 3 meses posparto: experiencia en un departamento de salud de la Comunidad Valenciana

Abstract: The prevalence of EBF at 3 months is low compared to other similar studies, although we see an upward trend. Belief in hypogalactia influenced the maintenance of exclusive breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
1
17
0
6
Order By: Relevance
“…The World Health Organization (WHO) recommend BF as the optimal feeding for all infants and exclusive breastfeeding (EBF) for the first 6 months of life; however, the rate of EBF in 4 months after delivery globally is still low (Victora et al, 2016). Despite these apparent benefits only about 36% of all infants are exclusively breastfed worldwide until approximately the age of 6 months (Victora et al, 2016;Vila-Candel et al, 2019). Many regions have different trends in the percentage of infants age 0-5 months exclusively breastfed, Eastern and Southern Africa 56%, South Asia 57%, North America 35%, and Eastern Europe and Central Asia 42% (UNICEF, 2019).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization (WHO) recommend BF as the optimal feeding for all infants and exclusive breastfeeding (EBF) for the first 6 months of life; however, the rate of EBF in 4 months after delivery globally is still low (Victora et al, 2016). Despite these apparent benefits only about 36% of all infants are exclusively breastfed worldwide until approximately the age of 6 months (Victora et al, 2016;Vila-Candel et al, 2019). Many regions have different trends in the percentage of infants age 0-5 months exclusively breastfed, Eastern and Southern Africa 56%, South Asia 57%, North America 35%, and Eastern Europe and Central Asia 42% (UNICEF, 2019).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Several reasons for this early cessation have been identified, including hypogalactia, newborn weight gain below the recommendations, lower maternal age, low socioeconomic status, level of maternal education, BF knowledge, intention, and self-efficacy BF, an unsupportive working environment, and negative maternal expectations or experience with BF (Oribe et al, 2015;Ramiro González et al, 2018;Vila-Candel et al, 2019).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Another study carried out in Valencia (Spain) observed that there was a relationship with breastfeeding time and maternal age, parity, low milk production, and low weight gain of the baby (7) .…”
Section: Introductionmentioning
confidence: 98%
“…A study carried out in the Federal District (Brazil) found that the causes for early weaning were related to the beliefs of weak milk and to the women’s need to return to work ( 6 ) . Another study carried out in Valencia (Spain) observed that there was a relationship with breastfeeding time and maternal age, parity, low milk production, and low weight gain of the baby ( 7 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Para o recém-nascido, os benefícios estão relacionados com imunização passiva, que protege contra infecções, como diarréias, pneumonias, meningites no primeiro ano de vida, redução da morte súbita, alergias, asma, obesidade. Para a mãe, além da melhoria do vínculo, ajuda na perda de peso, diminui a possibilidade de depressão, diminuição do sangramento pós-parto, proteção do câncer mama (3) .…”
Section: Introductionunclassified